Empirical Legal Studies Before 1940: A Bibliographic Essay - Kritzer, Herbert M (2009)
The modern empirical legal studies movement has well-known antecedents in the law and society and law and economics traditions of the latter half of the 20th century. Less well known is the body of empirical research on legal phenomena from the period prior to World War II. This paper is an extensive bibliographic essay that surveys the English language empirical legal research from approximately 1940 and earlier. The essay is arranged around the themes in the research: criminal justice, civil justice (general studies of civil litigation, auto accident litigation and compensation, divorce, small claims, jurisdiction and procedure, civil juries), debt and bankruptcy, banking, appellate courts, legal needs, legal profession (including legal education), and judicial staffing and selection. Accompanying the essay is an extensive bibliography of research articles, books, and reports